2012
DOI: 10.1103/physrevb.86.165303
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated molecular dynamics study of theGaAs(001)β2(2×4)/c(2×8)surface

Abstract: We develop an accelerated molecular dynamics method that has several advantages over conventional rare-event methods. We apply our method using a semiempirical Tersoff-Abell potential to understand the disordered structure of the GaAs(001)β2(2 × 4) surface at various temperatures. Our simulations indicate that the selfreconstruction of this surface is mediated by As-row-dimer and As-trench-dimer shifting events that typically occur over microsecond-millisecond times at temperatures of interest and that trench-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Additionally, the Tersoff and derived potentials have been widely compared to other experiments: Lajevardipour et al found that the room-temperature Young modulus of graphene (350 N m –1 ) was in close proximity to the experimental value (340 N m –1 ). Lin and Fichthorn found that the equilibrium surface of GaAs is in agreement with an experimental scanning–tunneling microscopy study. Ruthi et al found that the structural characterization of several III–IV zinc blende compound semiconductors was in excellent agreement with that determined by experiments.…”
Section: Methodssupporting
confidence: 70%
“…Additionally, the Tersoff and derived potentials have been widely compared to other experiments: Lajevardipour et al found that the room-temperature Young modulus of graphene (350 N m –1 ) was in close proximity to the experimental value (340 N m –1 ). Lin and Fichthorn found that the equilibrium surface of GaAs is in agreement with an experimental scanning–tunneling microscopy study. Ruthi et al found that the structural characterization of several III–IV zinc blende compound semiconductors was in excellent agreement with that determined by experiments.…”
Section: Methodssupporting
confidence: 70%
“…4. In this section, electron density difference Dr was dened as follows: r NO-graphene , r graphene , r NO , represents the total electron density of the adsorbed system, the electron density of the pure graphene, and the electron density of free state NO molecule, 39,40 respectively. In the ten sectional views, there were no overlaps of the electron density between a NO molecule and C atom.…”
Section: No Adsorption On Graphene Layermentioning
confidence: 99%
“…The CV-based flexibility of metadynamics, combined with the recent notion that it is able to describe system dynamics correctly, makes it a promising candidate for a more generally applicable bias potential-based accelerated MD method. Various hyperdynamics-based approaches have been developed precisely for this purpose, but these are usually specifically tailored to the (sub)­class of systems for which they were developed: the bias potential is dependent directly on a property of the studied system. In contrast, the biasing in a more general CV-based method such as metadynamics is dependent only on the CVs used, and applying it to a new system only requires changing the CVs, rather than adapting the overall method.…”
Section: Introductionmentioning
confidence: 99%